Paradigma Baru Pendidikan Tinggi dan Makna Kuliah Bagi Mahasiswa - Ahmad Taufiq (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
The quality of higher education institutions in Indonesia to date is still is low. This can be known when compared with institutions higher education in other countries. It is also known that there is the gap between the existing reality with the goals and standards of graduate competence universities that have been formulated in laws and regulations government and related universities. Many factors play a role in it. One is the paradigm education - including higher education - is becoming a community benchmark. This growing paradigm will then determine how students give meaning to the lecture that is being pursued. Meanwhile, meaning and any understanding they have about college, will determine their attitudes, behaviors, actions and activities in the process learning. And it will ultimately determine their success within learn. After quite a while, in the recent paradigm behavioristik become displaced by a new paradigm. The developing and the will be more established lately is a constructive paradigm. With referring to this paradigm, students become the central point in the process learning. Therefore, whatever meaning is given by the students of lectures will determine their attitudes and actions in following learning process. Furthermore, this meaning will determine success educational goals as will be achieved together.